Association of IL17 and IL23R gene polymorphisms with rheumatic heart disease in South Indian population. (3rd October 2018) - Poomarimuthu, Maheshkumar; Elango, Sivakumar; Solomon, Pravin Raj; Soundrapandian, Sambath; Mariakuttikan, Jayalakshmi
ABSTRACT: Background : IL-23/Th17 signaling pathway plays a crucial role in the cell-mediated immune response against bacterial infections and also in the pathogenesis of inflammatory and autoimmune diseases. Recent studies indicate that Th17 cell-associated cytokines are involved in the progression and maintenance of valvular lesions in rheumatic heart disease (RHD). Variants in the genes of cytokines that are potentially involved in Th17 response may influence interindividual differences in their expression levels, thereby contributing to the pathogenesis of immune-mediated diseases such as RHD. Objective : The aim of the study is to investigate the association of IL17A, IL17F, and IL23R gene variants with the risk perception of RHD. Methods : A total of 225 individuals (99 RHD patients and 126 healthy siblings) were recruited for the study. The IL17A (rs2275913), IL17F (rs763780), and IL23R (rs10889677) polymorphisms were determined by polymerase chain reaction restriction fragment length polymorphisms and amplification-refractory mutation system-polymerase chain reaction methods, respectively. Results : The frequency of IL17A (rs2275913) A/A genotype was significantly high in pooled RHD patients (odds ratio [OR] = 2.76; p c  = 0.021), rheumatic fever (RF) patients (OR = 14.5; p c  = 0.0001), and mitral valvular lesions patients (OR = 2.74; p c  = 0.039) when compared to healthy siblings. However, the IL17F (rs763780) and IL23R (rs10889677) polymorphisms did not show any association with RHD. Conclusions : The results suggest that IL17A (rs2275913) polymorphism is associated with the development of RF/RHD in South Indian population. Further studies are required to substantiate the association of these genes with the disease risk.